Experimental investigation of bio-improved laterite for use as a subgrade material in road construction - Reuben Orumah Sani; Tobi Vincent Ogunro; Isaac Ibukun Akinwumi (PLoS ONE, 2025)
This study investigated the application of microbial-induced calcite precipitation (MICP) using the bacterium Bacillus Anthracis for laterite subgrade soil improvement in road construction. The California bearing ratio (CBR), unconfined compressive strength (UCS), and hydraulic conductivity test were conducted on the bacterium-modified soil. A quasi-field comparative test was also carried out to assess the strength properties of the bio-cemented and natural laterite. According to the American Association of State Highway Officials, the natural soil was classified as A–6 (5), a fair to poor soil for use as a subgrade material, justifying the need for improvement. The natural soil’s CBR was improved by 80% at the 3 x 10 8 cells ml -1 treatment. The soil was improved from “very soft to soft” to “stiff to very stiff” soil for all Bacillus Anthracis treatments, and the natural soils’ UCS value increased by 191% at 3.0 × 10 8 cells ml -1 Bacillus Anthracis treatment, confirming the CBR results. Best improvements at 3 x 10 8 cells ml -1 of Bacillus Anthracis -treated soil provided better subgrade protection from water infiltration. Optimal bacterium-treated soil performed better in the field than in the laboratory. Results obtained successfully demonstrated the application of bio-improved laterite as a subgrade material for road construction.